Model Fit Determination of Marital Satisfaction Based on Self-Differentiation, Critical Thinking, and Emotional Self-Regulation Mediated by the Feeling of Happiness in Married Women - Kordbacheh , Soraya; Dokaneifard , Farideh; Nicknam , Mojgan (Applied Family Therapy Journal (AFTJ), 2024)
Objective: The primary objective of this study was to develop and validate a structural model of marital satisfaction among married women, based on self-differentiation, critical thinking, and emotional self-regulation, with happiness as a mediating variable.Methods and Materials: This study utilized a quantitative, descriptive-correlational design with a structural equation modeling (SEM) approach. The sample comprised married women who visited the counseling centers at the University of Tehran between January 2023 and August 2023. A total of 330 participants were selected using convenience sampling. Data were collected using validated questionnaires, including the Self-Differentiation Scale, Critical Thinking Questionnaire, Emotional Self-Regulation Scale, Oxford Happiness Questionnaire, and ENRICH Marital Satisfaction Scale. The data were analyzed using SEM to assess the model's fit and test the hypothesized relationships between variables.Findings: The results indicated that the proposed structural model fit the data well, with satisfactory model fit indices (χ²/df = 3.618, RMSEA = .061, CFI = .923). Self-differentiation (β = .217, p = .033), critical thinking (β = .230, p = .01), and emotional self-regulation (β = .201, p = .01) had significant direct effects on marital satisfaction. Additionally, happiness significantly mediated the relationships between self-differentiation (β = .229, p = .01), critical thinking (β = .178, p = .01), and emotional self-regulation (β = .200, p = .01) with marital satisfaction.Conclusion: This study underscores the importance of self-differentiation, critical thinking, and emotional self-regulation as key factors influencing marital satisfaction among married women. The mediating role of happiness highlights its significance in enhancing marital satisfaction by fostering positive emotions and reducing stress.